2021
DOI: 10.1108/jeim-11-2020-0449
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of supply chain flexibility on the relationship between supply chain integration and supply chain performance

Abstract: PurposeSupply chain integration (SCI) and flexibility (SCF) are recognised as crucial business practices and capability in the global competitive market. However, limited research has paid attention to study the relationship between SCI, SCF and their impact on supply chain performance (SCP). Therefore, the purpose of this paper is to establish a relationship between integration, flexibility and performance.Design/methodology/approachThe structural equation modelling technique was used to analyse the 187 data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 73 publications
5
30
4
Order By: Relevance
“…Specifically, the close cooperation network built by GSCI promotes deep communication among supply chain members and helps enterprises to search and acquire a large number of valuable resources, such as information, technology, and knowledge (Yang et al, 2020), thus playing an important role in promoting supply chain agility. Among them, green internal integration enhances communication within the organization and helps enterprises achieve a centralized allocation of resources to respond to environmental changes (Flynn et al, 2010;Khanuja and Jain, 2021), thereby improving supply chain agility. Green supplier and customer integration build a cooperative atmosphere of mutual trust among supply chain members, which enhances the closeness of the mutual relationship and helps shorten the transmission time and path of complementary resources in cooperation (Du et al, 2018;Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the close cooperation network built by GSCI promotes deep communication among supply chain members and helps enterprises to search and acquire a large number of valuable resources, such as information, technology, and knowledge (Yang et al, 2020), thus playing an important role in promoting supply chain agility. Among them, green internal integration enhances communication within the organization and helps enterprises achieve a centralized allocation of resources to respond to environmental changes (Flynn et al, 2010;Khanuja and Jain, 2021), thereby improving supply chain agility. Green supplier and customer integration build a cooperative atmosphere of mutual trust among supply chain members, which enhances the closeness of the mutual relationship and helps shorten the transmission time and path of complementary resources in cooperation (Du et al, 2018;Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Green internal integration breaks down departmental barriers within the organization, enhances communication and cooperation between different departments, and enables different departments to participate in and execute the operation plan of the enterprise as early as possible (Flynn et al, 2010;Shah and Soomro, 2021), which helps each department understand and grasp the firm's resources and capabilities, and optimize the firm's resources by cooperating. Therefore, it will help firms plan effectively to respond to dynamic market changes (Khanuja and Jain, 2021). At the same time, the collaborative atmosphere created by green internal integration enhances the emotional attachment and organizational commitment of employees (Shah and Soomro, 2021).…”
Section: Green Supply Chain Integration and Supply Chain Agilitymentioning
confidence: 99%
“…The existing literature has proved the positive effect of supply chain integration on innovation (Wong et al, 2013 ), flexibility (Khanuja & Jain, 2021 ), agility (Shukor et al, 2021 ), robustness (Zhuo et al, 2021 ) and responsiveness (Shukor et al, 2021 ), which are all conducive to improving the resilience capacity of firm operations (Ambulkar et al, 2015 ; Tukamuhabwa et al, 2015 ). Furthermore, Wijaya ( 2020 ) proposed that supplier integration and customer integration promote the consistency of business processes between firms and their supply chain partners and that internal integration promotes the coordination of functions, directly driving the development of resilience capability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Klevås (2005) notes that eco design & packaging enhances SCA as they have potential to influence all logistic activities. Yang et al (2020) argue that green supply chain integration impacts SCA by enabling an SC-wide integration of scattered resources in addition to promoting trust and interaction among SC partners that facilitate flow of information, another enabling condition for firms to make and orchestrate effective plans to respond to rising dynamism in the markets (Khanuja & Jain, 2022). Finally, Zhang et al (2022) found a positive effect of green internal, supplier and customer integration in enhancing supply chain agility.…”
Section: Green Initiatives and Scamentioning
confidence: 98%